Epidural Analgesia, Intrapartum Hyperthermia, and Neonatal Brain Injury: A Systematic Review and Meta-Analysis. Issue 1 (23rd March 2022) - Morton, S.; Kua, J.; Mullington, C.J.
Abstract : ( Br J Anaesth . 2021;126:500–515) Neonatal brain injury, a spectrum of diseases including neonatal encephalopathy and cerebral palsy, is caused by a number of factors. Intrapartum hypoxia and chorioamnionitis have both been associated with cerebral palsy. Evidence also suggests that epidural analgesia (EA) is associated with an increased risk of intrapartum hyperthermia. However, previous systematic reviews have shown that EA does not increase the risk of intrapartum infection, suggesting that epidural analgesia is a distinct condition. Growing evidence linking intrapartum hyperthermia and neonatal brain injury and recognizing epidural analgesia as a distinct condition has raised questions of whether EA is an independent risk factor of neonatal brain injury. This systematic review and meta-analysis was conducted to determine (1) if epidural analgesia is a cause of intrapartum hyperthermia, (2) if intrapartum hyperthermia is associated with neonatal brain injury and (3) if epidural analgesia is associated with neonatal brain injury.